Battery Sizing for Electric Vehicles Based on Real Driving Patterns in Thailand - Bongkotchaporn Duangsrikaew; Jiravan Mongkoltanatas; Chi-na Benyajati; Preecha Karin; Katsunori Hanamura (My University, 2019)
The rising population in suburban areas have led to an increasing demand for commuter buses. Coupled with a desire to reduce pollution from the daily routine of traveling and transportation, electric vehicles have become more interesting as an alternative placement for internal combustion engine vehicles. However, in comparison to those conventional vehicles, electric vehicles have an issue of limited driving range. One of the main challenges in designing electric vehicles (EVs) is to estimate the size and power of energy storage system, i.e., battery pack, for any specific application. Reliable information on energy consumption of vehicle of interest is therefore necessary for a successful EV implementation in terms of both performance and cost. However, energy consumption usually depends on several factors such as traffic conditions, driving cycle, velocities, road topology, etc. This paper presents an energy consumption analysis of electric vehicle in three different route types i.e., closed-area, inter-city, and local feeder operated by campus tram and shuttle bus. The driving data of NGV campus trams operating in a university located in suburban Bangkok and that of shuttle buses operating between local areas and en route to the city were collected and the corresponding representative driving cycles for each route were generated. The purpose of this study was to carry out a battery sizing based on the fulfilment of power requirements from the representative real driving pattern in Thailand. The real driving cycle data i.e., velocity and vehicle global position were collected through a GPS-based piece of equipment, VBOX. Three campus driving data types were gathered to achieve a suitable dimensioning of battery systems for electrified university public buses.
Keywords: Driving cycle; Driving range; Battery pack; Battery electric vehicle; Electric Vehicles and Infrastructure